Neuromuscular fatigue of cycling exercise in hypoxia - Mira, J.; Floreani, M.; Savoldelli, A.; Amery, K.; Koral, J.; Oranchuk, D. J.; Messonnier, L. A.; Rupp, T.; Millet, G. Y. (Medicine & Science in Sports & Exercise, 2020)
Introduction: The understanding of fatigue in hypoxia is limited due to: lack of control in arterial saturation, different exercise intensities and hypoxia levels, lag time between exercise cessation and fatigue evaluation. We aimed at evaluating fatigue during cycling and immediately after exhaustion (EXH) in normoxia, moderate and severe hypoxia at relative and absolute intensities.